2002
DOI: 10.1103/physrevlett.89.255502
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Response and Stiffening of Individual Multiwalled Carbon Nanotubes

Abstract: We report on the characterization of torsional oscillators which use multiwalled carbon nanotubes as the spring elements. Through atomic-force-microscope force-distance measurements we are able to apply torsional strains to the nanotubes and measure their torsional spring constants, and estimate their effective shear moduli. The data show that the nanotubes are stiffened by repeated flexing. We speculate that changes in the intershell mechanical coupling are responsible for the stiffening.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
111
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 22 publications
5
111
0
Order By: Relevance
“…The actuator properties of individual bending MWCNTs under an applied electric field have been studied experimentally [16]. The torsional actuation behavior of multiwalled tubes has also been reported [17,18]. These works are important but we note that all these studies focus on individual tubes and not a collection of tubes, nor their properties within a continuous elastic matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The actuator properties of individual bending MWCNTs under an applied electric field have been studied experimentally [16]. The torsional actuation behavior of multiwalled tubes has also been reported [17,18]. These works are important but we note that all these studies focus on individual tubes and not a collection of tubes, nor their properties within a continuous elastic matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Their extraordinary mechanical and electrical properties [2] ensure that CNTs will play an essential role in the design of nanoscale devices, such as nanotweezers [3], nanogears [4], nanotube motors [5], and axial nano-oscillators [6]. Recently, a nanoelectromechanical device [7][8][9] based on an individual CNT serving as a torsional spring and mechanical support has been successfully fabricated. Williams and co-workers [7,8] reported fabrication of nanoscale mechanical devices, which consist of a suspended lever, i.e., the ''paddle,'' connected by CNTs as torsion beams to stationary leads.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a nanoelectromechanical device [7][8][9] based on an individual CNT serving as a torsional spring and mechanical support has been successfully fabricated. Williams and co-workers [7,8] reported fabrication of nanoscale mechanical devices, which consist of a suspended lever, i.e., the ''paddle,'' connected by CNTs as torsion beams to stationary leads. Papadakis et al [9] used similar techniques to synthesize so-called torsional oscillators.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, nano-oscillators and actuators with MWCNTs in bending [1] and torsion [2,3] have been experimentally studied. In [1], the resonant frequencies of cantilevered MWCNTs excited electrically are reported.…”
mentioning
confidence: 99%
“…These nonbonded interactions are the only interlayer mechanical coupling in our simulations. Although it has been suggested that stronger coupling may occur [2], there is solid evidence of a weak interaction with very low sliding resistance like the one we adopt [3,15,16]. Equilibrium configurations are obtained by minimization of the total energy, i.e., the strain (bonded) energy plus the van der Waals energy.…”
mentioning
confidence: 99%